2020
DOI: 10.1101/2020.05.14.097204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression of ACE2 and TMPRSS2 proteins in the upper and lower aerodigestive tracts of rats

Abstract: Objective: Patients with coronavirus disease 2019 , caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), exhibit not only respiratory symptoms but also symptoms of chemo-sensitive disorders and kidney failure. Cellular entry of SARS-CoV-2 depends on the binding of its spike protein to a cellular receptor named angiotensinconverting enzyme 2 (ACE2), and the subsequent spike protein-priming by host cell proteases, including transmembrane protease serine 2 (TMPRSS2). Thus, high expression of AC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
0
20
0
3
Order By: Relevance
“…Furthermore, ACE2 high expression was demonstrated in the taste buds of rats and was associated with angiotensin II production in mice taste buds. These findings might also suggest the inability of ACE2 to degrade this protein during COVID-19 infection, resulting in disorderly taste responses (Shigemura et al 2019; Mariz et al 2020; Sato et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ACE2 high expression was demonstrated in the taste buds of rats and was associated with angiotensin II production in mice taste buds. These findings might also suggest the inability of ACE2 to degrade this protein during COVID-19 infection, resulting in disorderly taste responses (Shigemura et al 2019; Mariz et al 2020; Sato et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While ACE2 is expressed in the bronchial epithelium and in type 2 pneumocytes, TMPRSS2 results strongly expressed in the cytoplasm of bronchioles and alveolar epithelial cells (144). Since ACE2 was found to exist on alveolar epithelial cells at approximately similar level as in the whole lung, Sato et al found that the expression level of TMPRSS2 was considerably different between the peripheral and central parts of the lung (145). Thus, since that peripheral parts of the lung strongly express TMPRSS2, along with ACE2, the SARS-CoV-2 may be considered to damage the peripheral area at the beginning of infection.…”
Section: Lungsmentioning
confidence: 99%
“…Much less is known about the underlying mechanisms that may explain taste reduction in COVID-19. ACE2 is expressed in epithelial cells of the tongue ( Sato and others 2020 ; Vaira and others 2020c ; Xu and others 2020 ; Cooper and others 2020 ), but probably not in taste buds ( Wang and others 2020e ), yet ACE2 inhibitor drugs are known to induce taste (and smell) disorders ( Irvin and Viau 1986 ; Naik and others 2010 ; Bertlich and others 2020 ). In the olfactory epithelium, the evidence suggests a distinct cascade of cellular events that can explain the transient anosmia in COVID-19.…”
Section: Introductionmentioning
confidence: 99%